Study on micro thermodynamic process of gas flow in pulse tube by unequilibrium molecular dynamics simulations. (July 2019) - Qi, Yingxia; Che, Yanjin; Pan, Shuai; Zhang, Hua
Highlights: There is a natural frequency for gas oscillation in the tube. The micro process of formation of temperature gradient along the tube is revealed. The temperature difference along the tube is increased with the increase of length. The temperature difference along the tube is little varied with diameter under micro size. The mechanism of the micro scale pulse tube is investigated. Abstract: The micro thermodynamic process of gas flow in pulse tube is investigated by unequilibrium molecular dynamic simulations in this paper. To simulate the inflation and deflation processes of gas flow in the pulse tube, a constant-NVE ensemble is adopted. The simulation results show that the external pressure goes into the tube by a way of a sinusoidal wave. The real-time velocities and positions of every atom validate the kinetic formation process of the temperature gradient in axial direction. The amplitudes of the pressures, temperatures and mass-flow waves are increased with the increase of tube diameter but decreased with length. The period time is approximately linearly proportional to length but invariant with diameter. The cycle-averaged temperature difference along the tube is increased with the increase of length but less affected by diameter. It is conjectured that the optimum ratio (L/D) is increased with the increase of diameter. The results provide a basis for further optimizing COP and the lowest cooling temperature of the pulse tube refrigerator.